Design of PLC and EPICS based control system for a deuteron RFQ. (1st June 2022) - Liu, S.; Wei, Y.X.; Lu, Y.R.; Wang, Z.; Han, M.Y.; Wei, T.H.; Zheng, P.F.
Abstract: Peking University and Southwestern Institute of Physics are jointly developing a new deuteron RFQ to study the migration and deposition of impurities on the first wall of a tokamak facility. This RFQ will accelerate a 10-mA deuteron beam from 40 keV up to 1.5 MeV at a duty factor of 1%. In this paper, the detailed design of the prototype control system based on a Siemens PLC and EPICS/CSS software environment for the RFQ accelerator is presented. The system is composed by many kinds of sub-systems developed using different hardware solutions. The interlock protection mechanism is introduced into the control system. The EPICS Archiver Appliance is used to provide the service of data archiving and retrieval. The system has been successfully implemented for RF conditioning and beam commissioning.